A new approach for increasing graduate students’ science communication capacity and confidence - Erin R. Harrington; Scott R. McWilliams; Nancy E. Karraker; Caroline Gottschalk Druschke; Jenna Morton-Aiken; Elaine Finan; Ingrid E. Lofgren (PeerJ)
There is an increasing demand for emerging scientists to improve their ability to communicate with public audiences, yet little research investigates the effectiveness of science communication training for graduate students. We responded to this need by developing SciWrite@URI—an interdisciplinary model for science graduate students designed around three learning outcomes based on tenets from the field of writing and rhetoric—habitual writing, multiple genres, and frequent review. SciWrite students completed courses and a science communication internship, attended writing workshops, and became tutors at a newly established Graduate Writing Center. After 2 years of training, students more frequently wrote multiple drafts and engaged in peer review, increased their confidence as writers, and decreased their apprehension about writing. We conclude the tenets of the SciWrite program helped students improve as science communicators, and we make suggestions for effective ways graduate departments and training programs might implement and build on our model.